2021
DOI: 10.3390/jpm11030202
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequencing Results Disclosure in Diverse and Medically Underserved Populations: Themes, Challenges, and Strategies from the CSER Consortium

Abstract: Genomic sequencing results need to be effectively communicated across all populations and practice settings. Projects in the Clinical Sequencing Evidence-Generating Research (CSER) consortium enroll diverse racial/ethnic and medically underserved participants across various clinical contexts. This article explores a set of CSER results disclosure cases to expand the evidence base on experiences returning genomic results. Case details were collected using a structured set of questions. We identified common them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Other large precision medicine projects such as MyCode at Geisinger Health in collaboration with Regeneron Genetics Center, integrate the return of results process for pathogenic and likely pathogenic variants from a set list of genes found in the research setting into study participants current clinical care by placing the information into their electronic medical record and informing participant's clinical care team of the research results (40,46,47). Publications detailing the outcomes of these efforts (39)(40)(41)48), among others, will undoubtedly help to inform best practices in the future. These works on genomics return of results will also hopefully encourage discussions and engagement from all relevant stakeholders to develop return of results consensus guidelines for other omics in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other large precision medicine projects such as MyCode at Geisinger Health in collaboration with Regeneron Genetics Center, integrate the return of results process for pathogenic and likely pathogenic variants from a set list of genes found in the research setting into study participants current clinical care by placing the information into their electronic medical record and informing participant's clinical care team of the research results (40,46,47). Publications detailing the outcomes of these efforts (39)(40)(41)48), among others, will undoubtedly help to inform best practices in the future. These works on genomics return of results will also hopefully encourage discussions and engagement from all relevant stakeholders to develop return of results consensus guidelines for other omics in the future.…”
Section: Discussionmentioning
confidence: 99%
“…While feasibility of return is an important question for multi-omics return of results currently, multiple large precision medicine studies have plans or have begun returning medically actionable genetic sequencing results to study participants (39)(40)(41)(42)(43)(44). A well known example is the National Institute of Health (NIH)'s All of Us Research Project , which aims to genetically sequence one million people (42).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, we developed three novel measures of understanding to gain a more thorough and nuanced evaluation of parents' understanding of the GT results. We demonstrated that GUÍA specifically improved objective understanding of uncertain results, typically the most challenging to communicate due to the complex nature of the results, limited available data on the implications of the finding, and ambiguity surrounding the clinical significance and subsequent steps in medical management (20,31,32). We also note a significant impact on understanding in parents of children with IDD, a multifactorial disorder where the underlying etiology can be difficult to determine, suggesting GUÍA may have increased parents' understanding of results in the context of heightened clinical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Far fewer applications are focused on communicating GT results (post-test counseling) (18). Communicating GT results to patients can be challenging due to the complexity of the results, the degree of technical language used in clinical GT reports, the potential for misinterpretation, and the range of result types from benign to uncertain to pathogenic (19,20). Digital tools could potentially improve the communication of complex genetic results with features such as digital post-test educational modules, personalization, and visualization of results and medical recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Stakeholder input highlighted practical strategies the team had not considered, such as planning additional appointments to break-up discussion of complex topics and management. 25 Feedback groups Feedback groups are small groups of stakeholders who represent specific experience or demographic characteristics for targeted feedback regarding a research project idea, recruitment plans or challenges, data collection methods, relevance and format of an intervention, and feasibility of the proposed research workflows. Guided by a facilitator and often using predetermined questions based on projectspecific agendas, researchers can hold multiple feedback groups focused on the same topical agenda and/or different topical agendas at multiple points throughout the study.…”
Section: Consortium-level Community/patient Stakeholder Groupsmentioning
confidence: 99%